Tempted by her off-limits boss - Baine, Karin (Harlequin medical romance., 2025)
Veterinary nurse Eloise thought she had it all. But one messy divorce and empty nest later, she desperately needs a fresh start. Only, Eloise's move to the Highlands is soon derailed by an unexpected crush on her utterly gorgeous-and completely off-limits!-boss... Widowed vet Daniel has been adamantly keeping the world at arm's length since his painful loss. And yet his enchanting new employee seems determined to tempt him at every turn! Is it just the allure of a forbidden flirtation...or could this be a second shot at happy-ever-after?